Perceived Stress During the First Wave of COVID-19 Outbreak: Results From Nationwide Cross-Sectional Study in Estonia - Reile, Rainer; Kullamaa, Lembe; Hallik, Reeli; Innos, Kaire; Kukk, Maarja; Laidra, Kaia; Nurk, Eha; Tamson, Merili; Vorobjov, Sigrid (Frontiers in Public Health, 2021)
Objective: To study the population-level mental health responses during the first wave of coronavirus disease 2019 (COVID-19) outbreak in Estonia and analyse its socio-demographic, behavioral and health-related variations among general population. Methods: Study used nationally representative data on 4606 individuals, aged 18–79 years from a rapid-response cross-sectional survey conducted in April 2020. Point prevalence and mutually adjusted prevalence rate ratios for perceived stress from log-binomial regression analysis were presented for socio-demographic, behavioral and health-related variables. Results: Study found that 52.2% of population aged 18–79 reported elevated stress levels in relation to COVID-19 outbreak. Higher levels of perceived stress were found for women, in younger age groups, Estonians and for those with higher self-perceived infection risk, presence of respiratory symptoms and less-than-good self-rated health. Conclusion: Although the potential long-term health effects of current crisis are yet unknown, the alarmingly high stress levels indicate that COVID-19 pandemic has had widespread effect on populations’ mental health.